Strategi Pengembangan Usaha Sepuluh Wirausaha Muda Tenant Program IbK STIE Ahmad Dahlan Jakarta - Asriyal Asriyal; Sutia Budi (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2012)
The purpose of this study is to: (1) review and analyze the strategies that have been implemented by 10 young entrepreneur’s Program of IbK of STIEAD Jakarta in developing their businesses over the years; (2) identify and analyze the strategies that will be run by them for the next day; (3) analyze and formulate proposals for business development strategy is relevant to young entrepreneurs run by them. The results shows, the strategy which conducted by them is actually still conventional and little is applying modern business patterns. However, they have a plan/strategy development effort that started steady state. Targets that have been set should be reassessed and to be rationalized, if the strategy is capable of being implemented. The recommendations concerned are for all tenants should have self determination for entrepreneurship, able to instill confidence, and always looking for a way out in case of a deadlock